Self-assembling Janus dendritic polymer for gene delivery with low cytotoxicity and high gene transfection efficiency. Issue 39 (26th September 2016) - Ding, Sheng-Gang; Yu, Lei; Wang, Long-Hai; Wang, Lin-Ding; Yu, Zhi-Qiang; You, Ye-Zi
Abstract : Polycations have high DNA condensing ability, low immunogenicity, and great adaptability, which make them promising for gene delivery. Abstract : Polycations have high DNA condensing ability, low immunogenicity, and great adaptability, which make them promising for gene delivery. However, low transfection efficiency and inevitable toxicity are challenges of cationic polymers. In this study, we prepared a novel Janus dendritic polymer via a one-step Michael addition reaction of branched low-molecular-weight polyethylenimine (PEI, 1800 Da) and dendritic polythioether. The amphiphilic dendritic polymer can self-assemble into stable nanomicelles with high surface charge potential (+91.8 mV). The obtained nanomicelles can be used as a gene delivery vector, which exhibits a higher gene transfection efficiency and much lower cytotoxicity as compared with gold standard PEI (branched, 25 kDa).